Preservation of Blueschist-facies Minerals along a Shear Zone by Coupled Metasomatism and Fast-flowing CO2-bearing Fluids - Kleine, Barbara I.; Skelton, Alasdair D.L.; Huet, Benjamin; Pitcairn, Iain K.; et al. (Journal of Petrology, 2014)
Two types of blue halo (types I and II) composed of blueschist-facies minerals are centered around a brittle, normal shear zone in greenschist-facies rocks on the island of Syros, Aegean Sea, Greece. The shear zone is steeply dipping and cuts a near-horizontal layer of greenschist-facies rocks (albite + epidote + actinolite + chlorite + quartz). Type I and II blue haloes are 0·3 m and c. 1 m wide respectively, and are seen on both sides of the shear zone. The inner type I haloes are composed of nearly pure glaucophane schist and were formed by metasomatic addition of Na2O and SiO2, and to a lesser extent of K2O and large ion lithophile elements (LILE), coupled with loss of CaO, Al2O3 and MnO. The outer type II haloes consist of a carbonated blueschist-facies assemblage (glaucophane + calcite + phengite + epidote + garnet + quartz). These experienced only slight metasomatic changes (i.e. addition of K2O and LILE), which cannot alone explain halo formation. We present petrological, geochemical and thermodynamic evidence that this assemblage was preserved at greenschist-facies conditions because XCO2 was elevated by flow of a CO2-bearing fluid along the shear zone, which was approximately contemporaneous with greenschist-facies hydration in the surrounding rocks. We further note that the flux of CO2-bearing fluid along the shear zone was rapid with respect to the fluid flux in the surrounding rocks. Mass-balance calculations reveal that the fluid flux within the shear zone was at least 100–2000 times greater than the fluid flux within the surrounding rocks. Mineral textures show greenschist-facies minerals replacing blueschist minerals in the type II haloes, supporting our interpretation that the blueschist-facies minerals were preserved during greenschist-facies retrogression. A simplified P–T vs XCO2 pseudosection confirms that preservation of carbonated blueschist can occur at greenschist-facies conditions in the presence of a CO2-bearing flui
Keywords: blueschist preservation; fluid flux calculation; fluid–rock interaction; Si–Na metasomatism; thermodynamic modeling